Accuracy and Precision of Otolith‐Derived Age Interpretations for Known‐Age Lake Trout. (30th January 2022) - Osborne, Christopher A.; Robinson, Jason M.; Lantry, Brian F.; Weidel, Brian C.; Harding, Ian; Connerton, Michael J.
Abstract: Catch‐at‐age data are used to inform important management decisions for recovering populations of Lake Trout Salvelinus namaycush . Age data for Lake Trout are commonly derived from interpretation of annual growth marks (annuli) on the fish's otoliths. Due to the tendency for annuli to vary in appearance and the subjectivity that is inherent to any age interpretation method, it is important that the common sources of interpretation error be well understood for any aging method used to inform management plans. In this study, coded wire tags were used to establish true ages for 153 Lake Trout to measure the precision and accuracy of age interpretations made from transverse‐sectioned otoliths and to identify sources of potential age interpretation error that researchers and managers may encounter when using this method. Precision of age interpretations, as measured by average coefficient of variation, ranged from 7.9% to 9.2%. Accuracy of age interpretations varied among readers, with exact matches ranging from 41.8% to 53.6% and accuracy within ±1 year ranging from 81.0% to 83.0%. Age interpretation errors were more likely to be overestimates of true age for Lake Trout under age 7 and underestimates for Lake Trout over age 13. However, only reader 1 exhibited significant systematic bias in their age interpretations. Poor clarity of the first annuli, growth checks resembling annuli, and faintness of narrow annuli near otolith margins in older fish were identified as likely sources of interpretation error in this study. A digital reference collection of known‐age Lake Trout otoliths is provided as supplemental material in the online version of this article. This collection can be used for training new readers, measuring the accuracy of age interpretations, and monitoring for aging bias by anyone using otoliths to obtain age data for Lake Trout.